Spinopelvic Fixation Supplemented With Gullwing Plate for Multiplanar Sacral Fracture With Spinopelvic Dissociation: A Case Series With Short Term Follow Up - Mohd Asihin, Muhammad Azrin; Bajuri, Mohd Yazid; Ahmad, Abdul Rauf; Ganaisan, Premganesh K.; Fazir, Mohamad; Salim, Azizul Akram (Frontiers in Surgery, 2019)
We describe a series of three patients who sustained multiplanar sacral fractures with spinopelvic dissociation treated with bilateral triangle osteosynthesis supplemented with “gullwing” plate. Multiplanar sacral fracture causes the sacrum to divide into two parts which in severe cases, fracture displacement results in neurological injury. Spinopelvic fixation supplemented with “gullwing” plate surgical treatment is still a viable option with an acceptable outcome, despite delayed up to four weeks.